A structural health monitoring system of the overhead transmission line conductor - Long Zhao (Wiley, 2022)
Abstract Transmission lines are affected by aeolian vibration, sandstorms and acid rain, which cause structural damage and eventually lead to line breaking accidents. In this paper, the structural health monitoring technology of conductors is researched, and a structural monitoring system for conductors is designed. First, based on the structure of the ACSR (Aluminum Conductor Steel Reinforced) conductor and the dynamic equation, the relation between the natural frequencies and the structure of the conductor is obtained. Then, an online health monitoring system of the conductor structure is proposed, and key issues, such as the power supply solution of sensors, data preprocessing technology, multiple‐sensor synchronization method, are analyzed in detail. Finally, the structural health monitoring of overhead transmission lines designed in this paper is tested on 110‐kV experimental transmission lines. The experimental results show that from the system proposed the operation parameters of the conductors can be well obtained.